Changes in temperature of the ocular surface in the projection of the ciliary body in the early stages of induced non-infectious uveitis in rabbits (Ukrainian Journal of Ophthalmology, 2025)
Background: It is an important challenge to develop objective methods for assessing intraocular inflammation.Purpose: To determine temperatures of the ocular surface in the projection of the ciliary body in rabbits with induced non-infectious anterior and intermediate uveitis in the first five days of the disease.Material and Methods: Temperatures of the ocular surface in the projection of the ciliary body were determined in seventeen Chinchilla rabbits with induced non-infectious anterior and intermediate uveitis.Results: At day 1, there was significant difference in temperature of the ocular surface in the projection of the ciliary body between challenged eyes and eyes of intact rabbits (р=0.002) and between fellow eyes and eyes of intact rabbits (р=0.005), but not (р=0.12) between the challenged eye and the fellow eye (35.7°С (1.1) vs 35.0°С (0.9)). At day 3, temperature for the challenged eye was 36.0°С (0.7), and for the fellow eye, 34.9°С (0.5), and the difference was not significant (р = 0.09), but there was significant difference between challenged eyes and eyes of intact rabbits. At day 5, a significant difference in temperature of the ocular surface appeared between the challenged eye and the fellow eye (36.0°С (0.7) vs 34.7°С (0.5); р=0.04), and there was still a significant difference between challenged eyes and eyes of intact rabbits (р=0.008). There was no significant difference in body temperature  between challenged animals at day 1 and intact animals (39.1°С vs 39.1°С; р=0.75) and between challenged animals at day 3 and intact animals (39.2°С vs 39.1°С; р=0.58).Conclusion: On day 1 of induced non-infectious anterior and intermediate uveitis in rabbits, the temperature in ciliary body projection onto the ocular surface increased to 35.7°С (р = 0.002) for the challenged eyes and to 35.0°С (р=0.05) for the fellow eyes compared to eyes of intact rabbits, which is likely to be caused by the response of the autonomic nervous system in the presence of initiation of inflammatory process. On day 5, a significant difference appeared in the ocular surface temperature between the challenged eyes and fellow eyes (36.0°С vs 34.7°С; р = 0.04), which is likely to be caused by decreased temperature response of the autonomic nervous system as well as by a gradual decrease in temperature of the fellow eye.
Keywords: uveitis; objectively assess inflammation; ocular surface temperature